3,5,3′-Triiodothyronine–Loaded Liposomes Inhibit Hepatocarcinogenesis Via Inflammation-Associated Macrophages - Sun, Gangqi; Hou, Xiaojuan; Zhang, Luyao; Zhang, Hengyan; Shao, Changchun; Li, Fengwei; Zong, Chen; Li, Rong; Shi, Junxia; Yang, Xue; Zhang, Li (Frontiers in Oncology, 2022)
Abstract Background: Hepatocellular carcinoma (HCC) is an inflammation-related cancer. Abnormal activation and malignant transformation of hepatic progenitor cells (HPCs), driven by the inflammatory microenvironment, promotes hepatocarcinogenesis. Hepatic macrophages play an important role in the inflammatory microenvironment. Previous studies have suggested that L-3,5,3-triiodothyronine (T3) can regulate inflammation; however, its use is associated with serious cardiac side effects and its role in hepatocarcinogenesis remains unclear. In this study, we aimed to develop an effective and safe T3 delivery system and to explore its effects on HCC occurrence. Methods: T3 liposomes (T3-lipo) were prepared using the thin-film hydration method, and their characteristics, including particle size, polydispersity index (PDI), zeta potential, encapsulation efficiency (EE), drug loading (DL), drug release, and stability were evaluated in vitro. We assessed the effect of T3-lipo on hepatocarcinogenesis in diethylnitrosamine (DEN)-induced primary HCC in rats and examined the biodistribution of T3 and T3-lipo by High Performance Liquid Chromatography- Mass Spectrometry (HPLC-MS). Furthermore, we explored the potential molecular mechanism of T3-lipo in hepatocarcinogenesis by immunohistochemistry and immunofluorescence analyses, Bio-Plex assays, and real-time polymerase chain reaction analysis, and western blotting assays. Results: Compared to T3, T3-lipo had an enhanced inhibitory effect on hepatocarcinogenesis and reduced cardiac side effects in DEN-induced primary HCC in rats. T3-lipo attenuated inflammation in the liver and HPC activation. T3-lipo was absorbed by hepatic macrophages and regulated the secretion of inflammatory cytokines in macrophages by inhibiting inflammatory signaling pathways. Conclusions: T3-lipo may suppress hepatocarcinogenesis by regulating the inflammatory microenvironment in the liver without increasing the risk of cardiac side effects.